Optimalisasi Strategi Bauran Pemasaran dalam Meningkatkan Performa Penjualan pada UMKM (Studi Kasus Tahu Pak Eman) - Aida Komalasari; Palahudin Palahudin (MAMEN: Jurnal Manajemen, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in strengthening the local economy, particularly in the food industry. Tahu Pak Eman MSME is a home-based business focused on tofu production in Cigombong District, Bogor Regency. This study aims to examine the implementation of the marketing mix strategy at Tahu Pak Eman MSME and identify challenges faced in achieving sales targets. The approach used was a qualitative descriptive method through field observations, interviews with business owners, and documentation during the research activities. The research findings revealed that the implementation of the marketing mix at Tahu Pak Eman MSME is not yet fully effective, especially in product and promotion aspects. The quality of the tofu produced is adequate and stable, but the packaging is still simple and has not been optimally utilized as a marketing communication tool. In the area of ​​promotion, marketing activities still rely on word of mouth and have not maximized the use of digital media. Improvement steps taken during the study include developing a visual identity for the business, such as a logo, and utilizing social media and online ordering platforms as promotional channels. It is hoped that a more integrated marketing mix strategy can increase competitiveness, expand market coverage, and support Tahu Pak Eman MSME in achieving more stable revenue targets.